Ultraviolet light absorption antistatic fabric and preparation method thereof
By mixing modified polyester and modified nanotitanium dioxide and spinning and weaving, textile fabrics with excellent flame retardant, anti-static and ultraviolet resistance are prepared, which solves the problem of poor fabric performance in the prior art and realizes high-performance textile fabric production.
Patent Information
- Application Number
- CN202510139592.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to achieve excellent flame retardant performance, antistatic performance and ultraviolet resistance in textile fabrics at the same time, and the product performance is poor and the cost is high.
UV light absorption antistatic fabric was prepared by mixing modified polyester and modified nanotitanium dioxide and spinning and weaving. The modified polyester is obtained by reacting ethylene glycol, terephthalic acid and 2-dimethylaminoethylphosphoric acid and reacting with N-(2-bromoethyl)maleimide; the modified nanotitanium dioxide is obtained by reacting nanotitanium dioxide with 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-diformaldehyde, and reacting with resorcinol.
It achieves excellent flame retardant properties, anti-static properties and ultraviolet resistance of the fabric, while improving the mechanical properties of the fabric, meeting the demand for high-performance textiles in modern society.
Smart Images

Figure SMS_5 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of textile fabrics, in particular to an ultraviolet light absorbing antistatic fabric and a preparation method thereof. Background Art
[0002] The research and application of textiles are closely related to people's daily life and the development of related manufacturing industries. However, with the rapid development of economy and technology, people's lives have made great strides, and traditional fibers and fiber textiles can no longer meet the requirements of modern social development, nor can they meet people's requirements for the gradually improving quality of life. Textile fabrics are gradually developing from a single function to a multifunctional integrated direction. Textiles with a single flame retardant or anti-ultraviolet function are common in the market, and most of them use flame retardant or anti-ultraviolet functional finishing technology. This technical method has a simple process and low cost, but the product performance is poor and cannot reach the ideal. Therefore, the present invention prepares a UV-absorbing fabric with excellent flame retardant properties. Summary of the invention
[0003] The object of the present invention is to provide an ultraviolet light absorbing antistatic fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention discloses an ultraviolet light absorbing antistatic fabric, which is obtained by spinning and weaving modified polyester and modified nano titanium dioxide after mixing them evenly.
[0005] As an optimization, the modified polyester is obtained by reacting ethylene glycol, terephthalic acid and 2-dimethylaminoethyl phosphoric acid, and then reacting with N-(2-bromoethyl)maleimide.
[0006] As an optimization, the modified nano titanium dioxide is obtained by reacting nano titanium dioxide with 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-dicarboxaldehyde, and then reacting with resorcinol.
[0007] As an optimization, the nano titanium dioxide comes from Hebei Kexu Building Materials Co., Ltd.
[0008] A method for preparing an ultraviolet light absorbing antistatic fabric comprises the following preparation steps: (1) Mix nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide in a mass ratio of 1:(1.8~2.2):(50~60), stir at 20~30℃ and 100~200rpm for 20~30min, add 1H-pyrrole-2,5-dicarboxaldehyde (0.7~0.9 times the mass of nano-titanium dioxide), heat to 70~80℃ and continue stirring for 3~5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 3~5 times respectively, and dry at 75~85℃ for 8~10h , obtaining pre-modified nano titanium dioxide; mixing pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene in a mass ratio of 1:(1-3):(0.4-0.6):(38-42), stirring at 105-115°C and 200-300rpm for 9-11h, naturally cooling to room temperature, adding deionized water to adjust the pH to 1-3, standing for 20-40min and then filtering, washing with a 36-38% mass fraction hydrochloric acid aqueous solution and deionized water for 3-5 times respectively, and drying at 65-75°C for 10-12h to obtain modified nano titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethyl phosphoric acid and antimony trioxide are mixed in a mass ratio of 1: (1.7-1.9): (0.3-0.5): (0.01-0.02), stirred at 225-235°C and 100-200 rpm for 2-4 hours under a nitrogen environment, heated to 245-255°C and continued to stir for 2-4 hours, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol are mixed in a mass ratio of 1: (0.7-0.8): (3-4), stirred at 85-95°C and 200-300 rpm for 23-25 hours, naturally cooled to room temperature, filtered, washed with deionized water for 3-5 times, and dried at 55-65°C for 10-12 hours to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid are mixed in a mass ratio of 1:(0.03-0.05):(0.9-1.1):(3-5), stirred at 20-30°C and 200-300 rpm for 1-3 hours, and allowed to stand for 10-30 minutes to obtain a spinning solution, which is then subjected to electrospinning. After completion, the solution is allowed to stand at 80-90°C for 23-25 hours to obtain an ultraviolet light absorbing antistatic fiber; the ultraviolet light absorbing antistatic fiber is spun and woven by a textile machine to obtain an ultraviolet light absorbing antistatic fabric.
[0009] As an optimization, the reaction equation of the pre-modified nano-titanium dioxide in step (1) is: .
[0010] As an optimization, the reaction equation for modifying nano-titanium dioxide in step (1) is: .
[0011] As an optimization, the reaction equation of the pre-modified polyester in step (2) is: .
[0012] As an optimization, the reaction equation of the modified polyester in step (2) is: .
[0013] As an optimization, the electrospinning process parameters of step (3) are: spinning voltage 26 kV, receiving distance 6 cm, and pushing rate 0.003 mm / s.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the ultraviolet light absorbing antistatic fabric, the present invention comprises the following steps: reacting nano titanium dioxide with 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-dicarboxaldehyde, and then reacting with resorcinol to obtain modified nano titanium dioxide; reacting ethylene glycol, terephthalic acid and 2-dimethylaminoethyl phosphoric acid, and then reacting with N-(2-bromoethyl)maleimide to obtain modified polyester; and mixing the modified polyester and the modified nano titanium dioxide, spinning and weaving to prepare the ultraviolet light absorbing antistatic fabric.
[0015] Firstly, nano-titanium dioxide is reacted with 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-dicarboxaldehyde, and then reacted with resorcinol to obtain modified nano-titanium dioxide; 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-dicarboxaldehyde are deposited and polymerized on the nano-titanium dioxide through a Schiff base reaction, and a conjugated six-membered ring that can absorb ultraviolet light and react with oxygen and free radicals is introduced, thereby improving the anti-ultraviolet performance and flame retardant performance of the ultraviolet light absorbing antistatic fabric; at the same time, the diallyl structure on 1H-pyrrole-2,5-dicarboxaldehyde can be used as a reaction site for DA reaction to form a cross-linking structure, thereby improving the mechanical properties of the ultraviolet light absorbing antistatic fabric; and resorcinol is grafted by substitution reaction to form an ortho-hydroxyl group on the triazine ring, thereby promoting the transition of electronic energy levels and further improving the anti-ultraviolet performance of the ultraviolet light absorbing antistatic fabric.
[0016] Secondly, ethylene glycol, terephthalic acid and 2-dimethylaminoethyl phosphoric acid are reacted, and then reacted with N-(2-bromoethyl)maleimide to obtain modified polyester; the modified polyester and modified nano-titanium dioxide are mixed and then spun and woven to form ultraviolet light absorbing antistatic fabric; 2-dimethylaminoethyl phosphoric acid is used to participate in polyester polymerization, phosphorus element is introduced into the polyester main chain, and reacts with hydrogen and free radicals in the combustion product to improve the flame retardant property of ultraviolet light absorbing antistatic fabric; after grafting 2-dimethylaminoethyl phosphoric acid, the dimethylamino structure retained at the end can react with N-(2-bromoethyl)maleimide to form a quaternary ammonium salt structure, construct a conductive channel, and improve the antistatic property of the ultraviolet light absorbing antistatic fabric; at the same time, maleimide contains a diallyl structure and has two reaction sites participating in the DA reaction, which can form a cross-linking network and improve the mechanical properties of the ultraviolet light absorbing antistatic fabric. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0018] A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide were mixed at a mass ratio of 1:1.8:50, stirred at 20°C and 100 rpm for 30 min, 1H-pyrrole-2,5-dicarboxaldehyde (0.7 times the mass of nano-titanium dioxide) was added, the mixture was heated to 70°C and stirred for 5 h, cooled naturally to room temperature and filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried at 75°C for 1 h. 0h, to obtain pre-modified nano titanium dioxide; pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene were mixed in a mass ratio of 1:1:0.4:38, stirred at 105°C and 200rpm for 11h, naturally cooled to room temperature, deionized water was added to adjust the pH to 1, filtered after standing for 40min, washed with 36% hydrochloric acid aqueous solution and deionized water for 3 times respectively, and dried at 65°C for 12h to obtain modified nano titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethylphosphoric acid and antimony trioxide were mixed in a mass ratio of 1:1.7:0.3:0.01, stirred at 225°C and 100 rpm for 4 h under a nitrogen environment, heated to 245°C and continued to stir for 4 h, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:0.7:3, stirred at 85°C and 200 rpm for 25 h, naturally cooled to room temperature, filtered, washed with deionized water 3 times, and dried at 55°C for 12 h to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.03:0.9:3, stirred at 20°C and 200 rpm for 3 h, and allowed to stand for 30 min to obtain a spinning solution, which was then subjected to electrospinning. After completion, the solution was allowed to stand at 80°C for 25 h to obtain an ultraviolet light absorbing antistatic fiber. The ultraviolet light absorbing antistatic fiber was spun and woven by a textile machine to obtain an ultraviolet light absorbing antistatic fabric. Example 2
[0019] A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide were mixed in a mass ratio of 1:2:55, stirred at 25°C and 150 rpm for 25 min, 1H-pyrrole-2,5-dicarboxaldehyde (0.8 times the mass of nano-titanium dioxide) was added, the temperature was raised to 75°C and stirred for 4 h, the mixture was naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 80°C for 9 h. h, to obtain pre-modified nano titanium dioxide; the pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene were mixed in a mass ratio of 1:2:0.5:40, stirred at 110°C and 250rpm for 10h, cooled naturally to room temperature, added deionized water to adjust the pH to 2, allowed to stand for 30min and then filtered, washed with a 37% hydrochloric acid aqueous solution and deionized water for 4 times respectively, and dried at 70°C for 11h to obtain modified nano titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethylphosphoric acid and antimony trioxide were mixed in a mass ratio of 1:1.8:0.4:0.015, stirred at 230°C and 150 rpm for 3 h under a nitrogen environment, heated to 250°C and continued to stir for 3 h, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:0.75:3.5, stirred at 90°C and 250 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 60°C for 11 h to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.04:1:4, stirred at 25°C and 250 rpm for 2 hours, and allowed to stand for 20 minutes to obtain a spinning solution, which was then subjected to electrospinning. After completion, the solution was allowed to stand at 85°C for 24 hours to obtain ultraviolet light absorbing antistatic fibers. The ultraviolet light absorbing antistatic fibers were spun and woven by a textile machine to obtain ultraviolet light absorbing antistatic fabrics. Example 3
[0020] A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Mix nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide in a mass ratio of 1:2.2:60, stir at 30°C and 200 rpm for 20 min, add 1H-pyrrole-2,5-dicarboxaldehyde (0.9 times the mass of nano-titanium dioxide), heat to 80°C and continue stirring for 3 h, cool naturally to room temperature, filter, wash with anhydrous ethanol and deionized water for 5 times respectively, and dry at 85°C. 8h to obtain pre-modified nano titanium dioxide; pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene were mixed in a mass ratio of 1:3:0.6:42, stirred at 115°C and 300rpm for 9h, naturally cooled to room temperature, deionized water was added to adjust the pH to 3, filtered after standing for 20min, washed with 38% hydrochloric acid aqueous solution and deionized water for 5 times respectively, and dried at 75°C for 10h to obtain modified nano titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethyl phosphoric acid and antimony trioxide were mixed in a mass ratio of 1:1.9:0.5:0.02, stirred at 235°C and 200 rpm for 2 h under a nitrogen environment, heated to 255°C and continued to stir for 2 h, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:0.8:4, stirred at 95°C and 300 rpm for 23 h, naturally cooled to room temperature, filtered, washed with deionized water 5 times, and dried at 65°C for 10 h to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.05:1.1:5, stirred at 30°C and 300 rpm for 1 hour, and allowed to stand for 10 minutes to obtain a spinning solution, which was then subjected to electrospinning. After completion, the solution was allowed to stand at 90°C for 23 hours to obtain ultraviolet light absorbing antistatic fibers. The ultraviolet light absorbing antistatic fibers were spun and woven by a textile machine to obtain ultraviolet light absorbing antistatic fabrics.
[0021] Comparative Example 1 A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide were mixed in a mass ratio of 1:2:55, stirred at 25°C and 150 rpm for 25 min, 1H-pyrrole-2,5-dicarboxaldehyde (0.8 times the mass of nano-titanium dioxide) was added, the temperature was raised to 75°C and the stirring was continued for 4 h, the mixture was naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 80°C for 9 h to obtain modified nano-titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethylphosphoric acid and antimony trioxide were mixed in a mass ratio of 1:1.8:0.4:0.015, stirred at 230°C and 150 rpm for 3 h under a nitrogen environment, heated to 250°C and continued to stir for 3 h, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:0.75:3.5, stirred at 90°C and 250 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 60°C for 11 h to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.04:1:4, stirred at 25°C and 250 rpm for 2 hours, and allowed to stand for 20 minutes to obtain a spinning solution, which was then subjected to electrospinning. After completion, the solution was allowed to stand at 85°C for 24 hours to obtain ultraviolet light absorbing antistatic fibers. The ultraviolet light absorbing antistatic fibers were spun and woven by a textile machine to obtain ultraviolet light absorbing antistatic fabrics.
[0022] Comparative Example 2 A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Ethylene glycol, terephthalic acid, 2-dimethylaminoethyl phosphoric acid and antimony trioxide were mixed in a mass ratio of 1:1.8:0.4:0.015, stirred at 230°C and 150 rpm for 3 h under a nitrogen environment, heated to 250°C and continued to stir for 3 h, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:0.75:3.5, stirred at 90°C and 250 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water 4 times, and dried at 60°C for 11 h to obtain a modified polyester; (2) The modified polyester, nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.04:1:4, stirred at 25°C and 250 rpm for 2 hours, and allowed to stand for 20 minutes to obtain a spinning solution, which was then subjected to electrospinning. After completion, the mixture was allowed to stand at 85°C for 24 hours to obtain ultraviolet light absorbing antistatic fibers. The ultraviolet light absorbing antistatic fibers were spun and woven by a textile machine to obtain ultraviolet light absorbing antistatic fabrics.
[0023] Comparative Example 3 A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide were mixed in a mass ratio of 1:2:55, stirred at 25°C and 150 rpm for 25 min, 1H-pyrrole-2,5-dicarboxaldehyde (0.8 times the mass of nano-titanium dioxide) was added, the temperature was raised to 75°C and stirred for 4 h, the mixture was naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 80°C for 9 h. h, to obtain pre-modified nano titanium dioxide; the pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene were mixed in a mass ratio of 1:2:0.5:40, stirred at 110°C and 250rpm for 10h, cooled naturally to room temperature, added deionized water to adjust the pH to 2, allowed to stand for 30min and then filtered, washed with a 37% hydrochloric acid aqueous solution and deionized water for 4 times respectively, and dried at 70°C for 11h to obtain modified nano titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethyl phosphoric acid and antimony trioxide were mixed in a mass ratio of 1:1.8:0.4:0.015, stirred at 230°C and 150 rpm for 3 h under a nitrogen environment, heated to 250°C and continued to stir for 3 h, and naturally cooled to room temperature to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.04:1:4, stirred at 25°C and 250 rpm for 2 hours, and allowed to stand for 20 minutes to obtain a spinning solution, which was then subjected to electrospinning. After completion, the solution was allowed to stand at 85°C for 24 hours to obtain ultraviolet light absorbing antistatic fibers. The ultraviolet light absorbing antistatic fibers were spun and woven by a textile machine to obtain ultraviolet light absorbing antistatic fabrics.
[0024] Comparative Example 4 A method for preparing an ultraviolet light absorbing antistatic fabric, the method for preparing the ultraviolet light absorbing antistatic fabric comprising the following preparation steps: (1) Nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide were mixed in a mass ratio of 1:2:55, stirred at 25°C and 150 rpm for 25 min, 1H-pyrrole-2,5-dicarboxaldehyde (0.8 times the mass of nano-titanium dioxide) was added, the temperature was raised to 75°C and stirred for 4 h, the mixture was naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 80°C for 9 h. h, to obtain pre-modified nano titanium dioxide; the pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene were mixed in a mass ratio of 1:2:0.5:40, stirred at 110°C and 250rpm for 10h, cooled naturally to room temperature, added deionized water to adjust the pH to 2, allowed to stand for 30min and then filtered, washed with a 37% hydrochloric acid aqueous solution and deionized water for 4 times respectively, and dried at 70°C for 11h to obtain modified nano titanium dioxide; (2) Polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid were mixed in a mass ratio of 1:0.04:1:4, stirred at 25°C and 250 rpm for 2 hours, and allowed to stand for 20 minutes to obtain a spinning solution, which was then subjected to electrospinning. After completion, the mixture was allowed to stand at 85°C for 24 hours to obtain ultraviolet light absorbing antistatic fibers. The ultraviolet light absorbing antistatic fibers were spun and woven by a textile machine to obtain ultraviolet light absorbing antistatic fabrics.
[0025] Test Case 1. Flame retardancy Test method: The ultraviolet light absorbing antistatic fabrics obtained in each embodiment and the comparative example were cut into samples of 150 mm×58 mm in size, and the limiting oxygen index was tested according to GB / T5454.
[0026] 2. Mechanical properties and UV resistance Mechanical properties testing method: The ultraviolet light absorbing antistatic fabrics obtained in each embodiment and the comparative example were cut into samples of 6 cm × 20 cm in size, and the warp breaking strength σ0 was tested at 20 mm / min using a WDW3020 electronic universal material testing machine in accordance with GB / T3923.
[0027] UV resistance test method: The UV-absorbing antistatic fabrics obtained in each example and the comparative example were cut into samples of 6 cm × 20 cm in size, placed flat in the sample tray of the textile UV accelerated aging tester, and tested at 50 ° C, 0.89 W / m 2 Leave it to stand for 50 hours under the same conditions, take it out to test the breaking strength σ1, and calculate the strength retention rate = σ0-σ1 / σ0*100%.
[0028] 3. Antistatic properties Test method: The UV-absorbing antistatic fabrics obtained in each embodiment and the comparative example were placed at 23°C and 48% relative humidity for 24 hours according to GB / T12703, and the resistance values were measured using a PRS-801 surface resistance tester.
[0029] Table 1 below shows the analysis results of the flame retardancy, antistatic property, UV resistance and mechanical properties of the ultraviolet light absorbing antistatic fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0030] Table 1
[0031] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the ultraviolet light absorbing antistatic fabric prepared by the present invention has good flame retardancy, antistatic property, ultraviolet resistance and mechanical properties.
[0032] By comparison, the strength retention rates of Examples 1, 2, and 3 are higher than those of Comparative Example 1, indicating that the substitution reaction is used to graft resorcinol to form ortho-hydroxyl groups on the triazine ring, thereby promoting the transition of electron energy levels and improving the anti-ultraviolet performance of the ultraviolet light absorbing antistatic fabric.
[0033] By comparison, the limiting oxygen index, strength retention rate and breaking strength of Examples 1, 2 and 3 are higher than those of Comparative Example 2, which indicates that 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-dicarboxaldehyde are deposited and polymerized on nano-titanium dioxide through the Schiff base reaction, and a conjugated six-membered ring that can absorb ultraviolet light and react with oxygen and free radicals is introduced, thereby improving the anti-ultraviolet and flame retardant properties of the ultraviolet light absorbing antistatic fabric; at the same time, the diallyl structure on 1H-pyrrole-2,5-dicarboxaldehyde can be used as a reaction site for the DA reaction to form a cross-linked structure, thereby improving the mechanical properties of the ultraviolet light absorbing antistatic fabric.
[0034] By comparison, Examples 1, 2, and 3 have lower resistance and higher breaking strength than Comparative Example 3, indicating that after grafting 2-dimethylaminoethyl phosphoric acid, the dimethylamino structure retained at the end can react with N-(2-bromoethyl)maleimide to form a quaternary ammonium salt structure, construct a conductive channel, and improve the antistatic properties of the ultraviolet light absorbing antistatic fabric; at the same time, maleimide contains a bisallyl structure and has two reaction sites participating in the DA reaction, which can form a cross-linked network and improve the mechanical properties of the ultraviolet light absorbing antistatic fabric.
[0035] By comparison, Examples 1, 2, and 3 have higher limiting oxygen index and breaking strength and lower resistance than Comparative Example 4, which illustrates that 2-dimethylaminoethyl phosphoric acid is used to participate in polyester polymerization, and phosphorus is introduced into the polyester main chain to react with hydrogen and free radicals in the combustion products to improve the flame retardant properties of the ultraviolet light absorbing antistatic fabric.
[0036] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A UV-absorbing antistatic fabric, characterized in that: The ultraviolet light absorbing antistatic fabric is obtained by mixing modified polyester and modified nano titanium dioxide and spinning and weaving them; The modified polyester is obtained by reacting ethylene glycol, terephthalic acid and 2-dimethylaminoethyl phosphoric acid, and then reacting with N-(2-bromoethyl)maleimide; The modified nano titanium dioxide is obtained by reacting nano titanium dioxide with 2-chloro-4,6-diamino-1,3,5-triazine and 1H-pyrrole-2,5-dicarboxaldehyde and then with resorcinol.
2. A method for preparing an ultraviolet light absorbing antistatic fabric, characterized in that: The method comprises the following preparation steps: (1) Mix nano-titanium dioxide, 2-chloro-4,6-diamino-1,3,5-triazine and N,N-dimethylformamide in a mass ratio of 1:(1.8~2.2):(50~60), stir at 20~30℃ and 100~200rpm for 20~30min, add 1H-pyrrole-2,5-dicarboxaldehyde (0.7~0.9 times the mass of nano-titanium dioxide), heat to 70~80℃ and continue stirring for 3~5h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 3~5 times respectively, and dry at 75~85℃ for 8~10h , obtaining pre-modified nano titanium dioxide; mixing pre-modified nano titanium dioxide, resorcinol, aluminum chloride and chlorobenzene in a mass ratio of 1:(1-3):(0.4-0.6):(38-42), stirring at 105-115°C and 200-300rpm for 9-11h, naturally cooling to room temperature, adding deionized water to adjust the pH to 1-3, standing for 20-40min and then filtering, washing with a 36-38% mass fraction hydrochloric acid aqueous solution and deionized water for 3-5 times respectively, and drying at 65-75°C for 10-12h to obtain modified nano titanium dioxide; (2) Ethylene glycol, terephthalic acid, 2-dimethylaminoethyl phosphoric acid and antimony trioxide are mixed in a mass ratio of 1: (1.7-1.9): (0.3-0.5): (0.01-0.02), stirred at 225-235°C and 100-200 rpm for 2-4 hours under a nitrogen environment, heated to 245-255°C and continued to stir for 2-4 hours, and naturally cooled to room temperature to obtain a pre-modified polyester; the pre-modified polyester, N-(2-bromoethyl)maleimide and anhydrous ethanol are mixed in a mass ratio of 1: (0.7-0.8): (3-4), stirred at 85-95°C and 200-300 rpm for 23-25 hours, naturally cooled to room temperature, filtered, washed with deionized water for 3-5 times, and dried at 55-65°C for 10-12 hours to obtain a modified polyester; (3) The modified polyester, modified nano-titanium dioxide, dichloromethane and trifluoroacetic acid are mixed in a mass ratio of 1:(0.03-0.05):(0.9-1.1):(3-5), stirred at 20-30°C and 200-300 rpm for 1-3 hours, and allowed to stand for 10-30 minutes to obtain a spinning solution, which is then subjected to electrospinning. After completion, the solution is allowed to stand at 80-90°C for 23-25 hours to obtain an ultraviolet light absorbing antistatic fiber; the ultraviolet light absorbing antistatic fiber is spun and woven by a textile machine to obtain an ultraviolet light absorbing antistatic fabric.
3. The method for preparing a UV-absorbing antistatic fabric according to claim 2, characterized in that: The reaction equation of the pre-modified nano titanium dioxide in step (1) is: 。 4. The method for preparing a UV-absorbing antistatic fabric according to claim 2, characterized in that: The reaction equation for modifying nano titanium dioxide in step (1) is: 。 5. The method for preparing a UV-absorbing antistatic fabric according to claim 2, characterized in that: The reaction equation of the pre-modified polyester in step (2) is: 。 6. The method for preparing a UV-absorbing antistatic fabric according to claim 2, characterized in that: The reaction equation of the modified polyester in step (2) is: 。 7. The method for preparing a UV-absorbing antistatic fabric according to claim 2, characterized in that: The electrospinning process parameters in step (3) are: spinning voltage 26 kV, receiving distance 6 cm, and pushing rate 0.003 mm / s.
Citation Information
Patent Citations
Light anti-ultraviolet fabric and preparation method thereof
CN113089310A
Multifunctional anti-aging polycarbonate fiber membrane material and preparation method thereof
CN113564748A
Multifunctional coating with super-strong mechanical property and self-repairing function
CN116200116A
Preparation method of antistatic wear-resistant polyester fiber fabric
CN119061521A
Flame-retardant antistatic wear-resistant fabric and preparation method thereof
CN119121444A